Land Subsidence Susceptibility Projection for Palembang Slum Area by Complex MCDM-AHP Technique - Siti Noratiqah Mohamad Deros; Norashidah Md Din; Syamimi Mohd Norzeli; Rohayu Che Omar; Fathoni Usman; Sumie Amariena Hamim (Journal of Engineering and Technological Sciences, 2022)
Land subsidence is a geomorphological event that affects Earth’s structure and physiognomy. This phenomenon occurs when the groundwater volume changes and results in the movement and sinking of sediment. Several studies have been conducted to identify major causes or factors that may lead to land subsidence. It was found that land subsidence intensity is influenced by several factors, i.e. terrain slope and aspect, land use, soil moisture content, and distance to a river. Population density contributes to continuous changes in land use. Deep investigation of factors that contribute to land subsidence such as population density is important. This study investigated the relationship between land subsidence and population density contributing to continuous land-use changes. The study area was a highly populated slum area along the Musi River in Palembang, Indonesia. Factors that have high contribution to land subsidence were considered in developing a land subsidence susceptibility map. Susceptibility analysis was done using the Analytical Hierarchy Process (AHP) method. Land subsidence features were associated with slum features and the result revealed a significantly high correlation (r = 0.844) between actual land subsidence areas and the developed susceptibility map.